The reservoir tapes - McGregor, Jon, 1976-; McGregor, Jon, 1976- (New York : Catapult, 2018)
Returns to the territory of the author's "Reservoir 13," tracing the efforts of an interviewer who collects stories throughout a secretive English village to piece together the fate of a missing girl.
Keywords: Missing persons -- Fiction; Violence -- Fiction; Missing persons -- Fiction; Violence -- Fiction; Great Britain -- Fiction; Great Britain -- Fiction; Mystery fiction; Short stories; Mystery fiction; Short stories